Adverse effects of oral second-line antituberculosis drugs in children. Issue 10 (2nd October 2016) - Schaaf, H. Simon; Thee, Stephanie; van der Laan, Louvina; Hesseling, Anneke C.; Garcia-Prats, Anthony J.
ABSTRACT: Introduction : Increasing numbers of children with drug-resistant tuberculosis are accessing second-line antituberculosis drugs; these are more toxic than first-line drugs. Little is known about the safety of new antituberculosis drugs in children. Knowledge of adverse effects, and how to assess and manage these, is important to ensure good adherence and treatment outcomes. Areas covered : A Pubmed search was performed to identify articles addressing adverse effects of second-line antituberculosis drugs; a general search was done for the new drugs delamanid and bedaquiline. This review discusses adverse effects associated with oral second-line antituberculosis drugs. The spectrum of adverse effects caused by antituberculosis drugs is wide; the majority are mild or moderate, but these are important to manage as it could lead to non-adherence to treatment. Adverse effects may be more common in HIV-infected than in HIV-uninfected children. Expert opinion : Although children may experience fewer adverse effects from oral second-line antituberculosis drugs than adults, evidence from prospective studies of the incidence of adverse events in children is limited. Higher doses of second-line drugs, new antituberculosis drugs, and new drug regimens are being evaluated in children: these call for strict pharmacovigilance in children treated in the near future, as adverse effect profiles may change.